Thalamic involvement in a patient with kernicterus - (:unkn) unknown (SPRINGER-VERLAG, 2002)
We report the MR imaging findings of a 16-month-old boy with dyskinetic cerebral palsy resulting from kernicterus. T2-weighted images showed symmetric bilateral hyperintensity in the thalamus in addition to the globus pallidus.
Keywords: kernicterus; thalamus; MR imaging; MR FINDINGS; HYPERBILIRUBINEMIA